Aging of reticulated Si-SiC foams in porous burners - Ortona, Alberto; Pusterla, Simone; Fino, Paolo; Mach, Alexander; Delgado, Antonio; Biamino, Sara (Advances in Applied Ceramics, 2010)
Abstract Si-SiC open cell foams with porosity >87% and high pore sizes (4-7 mm) are commonly employed as active zone in porous burners for heat radiation applications. In a porous burner, the solid porous body let the heat recirculate from the hot combustion products to the incoming reactants. The result is that the flame is confined within the foam, meaning high thermomechanical loadings on its constituent material. A set of commercial Si-SiC foams from the same production batch was aged with flat porous burners. Thermal cycles ramp-up, dwell and cooling, as well as burner set-up (power: 15 kW, fuel/air ratio: 1•5), were chosen based on previous experience. Before aging, each foam was first cut in bars ready for bending tests, reassembled into the burner foam configuration and operated. As produced and aged samples were physically, mechanically and chemically analysed and results compared. © 2010 Institute of Materials, Minerals and MiningPublished by Maney on behalf of the Institute.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.agingo
Keywords: Mechanical properties; Porous ceramics; SiC; Thermal applications